2021
DOI: 10.3390/metabo11120828
|View full text |Cite
|
Sign up to set email alerts
|

Serum Branched-Chain Amino Acid Metabolites Increase in Males When Aerobic Exercise Is Initiated with Low Muscle Glycogen

Abstract: This study used global metabolomics to identify metabolic factors that might contribute to muscle anabolic resistance, which develops when aerobic exercise is initiated with low muscle glycogen using global metabolomics. Eleven men completed this randomized, crossover study, completing two cycle ergometry glycogen depletion trials, followed by 24 h of isocaloric refeeding to elicit low (LOW; 1.5 g/kg carbohydrate, 3.0 g/kg fat) or adequate (AD; 6.0 g/kg carbohydrate 1.0 g/kg fat) glycogen. Participants then pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
0
24
1
Order By: Relevance
“…Both long‐chain and dicarboxylate fatty acid metabolites are important for energy generation through β‐oxidation and ω‐oxidation, respectively (Miura, 2013; Nakamura et al, 2014). Reductions in these metabolites are contrary to previous studies from our laboratory (Karl et al, 2017; Margolis et al, 2021) and others (Nieman et al, 2013; Stander et al, 2018), which reported increases in long‐chain and dicarboxylate fatty acid metabolites following acute aerobic exercise (4 h) or sustained military training (3 days). It is possible that declines in these metabolites may be the result of reductions in the relative dietary fat intake that were observed using an FFQ.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Both long‐chain and dicarboxylate fatty acid metabolites are important for energy generation through β‐oxidation and ω‐oxidation, respectively (Miura, 2013; Nakamura et al, 2014). Reductions in these metabolites are contrary to previous studies from our laboratory (Karl et al, 2017; Margolis et al, 2021) and others (Nieman et al, 2013; Stander et al, 2018), which reported increases in long‐chain and dicarboxylate fatty acid metabolites following acute aerobic exercise (4 h) or sustained military training (3 days). It is possible that declines in these metabolites may be the result of reductions in the relative dietary fat intake that were observed using an FFQ.…”
Section: Discussioncontrasting
confidence: 98%
“…More likely, changes in fat metabolites are related to the ~2 kg decrease in FM during IMT, with discrepancies between the past and current studies due to the state in which serum samples were collected and the study duration. In previous studies, increases in metabolites were reflective of a post aerobic exercise state (Karl et al, 2017; Margolis et al, 2021; Nieman et al, 2013; Stander et al, 2018), wherein increased concentrations of serum long‐chain and dicarboxylate fatty acid metabolites are likely reflective of increases in lipolysis to augment substrate availability for oxidation in skeletal muscle (Karl et al, 2017; Margolis et al, 2021). In the current study, serum was collected under resting fasted conditions and likely reflected longer‐term adaptation including reductions in total body FM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another interesting phenomenon in our study was that the differences in sports level and serum metabolome also have gender characteristics. In some studies on sports ability and differential metabolites, the participants involved were generally one gender ( Kim et al, 2013 ; San-Millán et al, 2020 ; Margolis et al, 2021 ) or a total of men and women ( Gervasi et al, 2020 ); however, few studies focused on gender characteristics. There was a study on the changes in fat-free mass and plasma amino acids of male and female recruits after military training ( Margolis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…He uses an integrative, translation approach, assessing whole-body metabolism and skeletal muscle molecular responses to exercise, nutritional manipulation and exposure to environmental extremes. , produces negative protein balance (Margolis et al, 2016;Margolis, Murphy et al, 2014;Pasiakos et al, 2013) and alters substrate metabolism (Karl et al, 2017;Margolis et al, 2019;Margolis, Karl et al, 2021;. The underlying mechanisms mediating these effects of low energy and glycogen availability remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%